PET (Polyethylene Terephthalate) film with hot melt adhesive on two sides and preparation method thereof

By applying the adhesion layer on both sides of the PET film and compounding the modified EVA adhesive layer, the problem of weak bonding force between the EVA hot melt adhesive and the PET film is solved, and the bonding strength and aging resistance are improved, especially the material stability in high humidity and heat and ultraviolet rays.

CN120329882APending Publication Date: 2025-07-18HUIZHOU YIDU STATIONERY SUPPLIES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510651858.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-20
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

The direct interface bonding force of the existing EVA hot melt adhesive and PET film is not strong, resulting in insufficient bonding strength and poor humidity and heat aging resistance and ultraviolet resistance.

Method used

The adhesion layer is coated on both sides of the PET substrate, and the modified EVA adhesive layer is coated on the outer side of the adhesion layer. The modified EVA adhesive layer is blended by EMA resin and petroleum resin, and modified substances such as zinc borate-silica hybrid capsules and dopamine derivative-graphene quantum dot composites are added to enhance the adhesive properties and aging resistance.

Benefits of technology

It improves the toughness and stiffness of the PET film, enhances the adhesion under high and low temperatures, high humidity and other conditions, improves the adhesive performance and aging resistance, especially the material stability under humidity and heat and ultraviolet aging conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120329882A_ABST
    Figure CN120329882A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and discloses a PET film with hot melt adhesives on two sides and a preparation method thereof.The PET film with the hot melt adhesives on the two sides comprises a PET base material, the two sides of the PET base material are coated with adhesive force layers, the outer sides of the adhesive force layers are coated with composite modified EVA adhesive layers, the adhesive force layers are made of water-based acrylate modified polyurethane emulsion, and the water-based acrylate modified polyurethane emulsion is coated with the hot melt adhesives on the two sides. The modified EVA adhesive layer is prepared from the following raw materials: EVA resin, EMA resin, petroleum resin, MAH-g-EVA, microcrystalline wax, zinc borate-organic silicon hybrid capsules, a dopamine derivative-graphene quantum dot compound and an antioxidant. According to the PET film adhesive force layer with the hot melt adhesive on the two sides, the adhesive force of the modified EVA adhesive layer to a PET layer base material under the conditions of high temperature, low temperature, high humidity and the like can be guaranteed, and the modified EVA adhesive layer has good adhesive performance and aging resistance through blending modification and addition of a modification additive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of polymer materials, and particularly relates to a PET film with hot melt adhesive on both sides and a preparation method thereof. Background Art

[0002] Hot melt adhesive, also known as hot melt glue, is a solvent-free thermoplastic solid adhesive. When in use, it obtains fluidity after being heated and melted, infiltrates the surface of the adherend, and can achieve adhesion after hardening or reaction curing upon cooling. Compared with other adhesives, hot melt glue has the characteristics of fast bonding speed, can be cured within seconds when heated and melted and contacted with the surface of the adherend, and is suitable for automated and continuous production processes; it contains no solvent, is non-toxic to the human body, does not pollute the environment, and is convenient for transportation and storage; it can bond a variety of materials, and can be used to bond wood, paper, metal, glass, plastic, ceramic, clothing materials, electronic components, packaging materials, etc., and can even bond materials such as wax paper that are difficult to bond with other adhesives; it has strong chemical resistance and can resist the erosion of water, brine, oil, acid, alkali, gasoline, etc.; it can be reheated and used. When the hot melt glue applied to the adherend cannot bond due to cooling and hardening, or when the bonding part needs to be changed, it can be reheated for bonding operations and other characteristics.

[0003] EVA hot melt adhesive material is a green thermoplastic adhesive prepared by melt blending with hot melt grade EVA resin as the base material, tackifying resin, wax, filler, etc. as additives. Due to the excellent properties of EVA resin, EVA hot melt adhesive has now become the most common adhesive. It has more types than similar polymer hot melt adhesives and a wider application range than any other adhesive, and is suitable for bonding various fabrics, shoe soles, nylon fabrics, water-repellent materials, leather, polyester fibers, polymer materials, and metals. However, when using a single layer of EVA hot melt adhesive for bonding materials, its toughness and stiffness are insufficient. When using EVA hot melt adhesive composite PET film, although the problem of insufficient toughness and stiffness can be solved, the direct interfacial bonding force between EVA hot melt adhesive and PET film is not strong, thus reducing the bonding strength of the hot melt adhesive. In addition, EVA hot melt adhesive itself also has problems of poor resistance to wet heat aging and ultraviolet resistance. Therefore, the bonding performance of the hot melt adhesive is greatly affected by environmental changes. Summary of the Invention

[0004] To solve the deficiencies mentioned in the above background art, the purpose of the present invention is to provide a PET film with hot melt adhesive on both sides and a preparation method thereof. The PET substrate is compounded and modified with an EVA adhesive layer through an adhesion layer to ensure the adhesion of the modified EVA adhesive layer to the PET layer substrate under high and low temperatures, high humidity, etc. The modified EVA adhesive layer is blended with EMA resin and petroleum resin, and modified substances such as zinc borate - organosilicon hybrid capsules and dopamine derivative - graphene quantum dot composites are added, so that the modified EVA adhesive layer has good bonding performance and aging resistance.

[0005] The object of the present invention can be achieved by the following technical solutions: A PET film with hot melt adhesive on both sides, comprising a PET substrate, with an adhesion layer coated on both sides of the PET substrate, and a modified EVA adhesive layer laminated and compounded on the outside of the adhesion layer. The adhesion layer is an aqueous acrylate-modified polyurethane emulsion. The modified EVA adhesive layer comprises the following raw materials in parts by weight: 60-80 parts of EVA resin, 15-20 parts of EMA resin, 20-25 parts of petroleum resin, 4-6 parts of MAH-g-EVA, 8-10 parts of microcrystalline wax, 5-8 parts of zinc borate-silicone hybrid capsules, 3-5 parts of dopamine derivative-graphene quantum dot composite, and 0.5-1 part of antioxidant; The zinc borate-silicone hybrid capsules are prepared by loading zinc borate nanoparticles with mesoporous silica as a template, grafting a vinyl-containing silane coupling agent on the surface, and then encapsulating them into 1-2 μm capsules through microemulsion technology; The dopamine derivative-graphene quantum dot composite is prepared by condensing dopamine with lauric acid to form an amphoteric polymer, and then loading nitrogen-doped graphene quantum dots through π-π stacking self-assembly.

[0006] Preferably, the aqueous acrylate-modified polyurethane emulsion is obtained by mixing acrylate monomers with a polyurethane emulsion and then adding ammonium persulfate to initiate a polymerization reaction.

[0007] Preferably, the antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 3-4:1.

[0008] Preferably, the preparation method of the zinc borate-silicone hybrid capsules comprises the following steps: A1. Immerse mesoporous silica in an ethanol solution of 0.1M zinc nitrate and 0.2M boric acid, adjust the pH to 6.5 with acetic acid, ultrasonicate for 20-40 min, and perform a hydrothermal reaction at 80 °C for 4-6 h to form zinc borate-loaded nanoparticles; A2. Disperse the above nanoparticles in an ethanol solution of vinyltrimethoxysilane, add ammonia water for catalysis, and reflux at 60 °C for 10-12 h to obtain surface-modified nanoparticles; A3. Disperse the surface-modified nanoparticles in paraffin oil at a mass ratio of 1:2.5 to obtain an oil phase, mix a 1wt% polyvinyl alcohol solution and a 0.5wt% sodium dodecyl sulfate solution to obtain an aqueous phase, adjust the pH of the aqueous phase to 4-5 with acetic acid, then mix the oil phase and the aqueous phase at a volume ratio of 1:4, add an emulsifier composed of span 80 and tween 80 at a volume ratio of 7:3, perform high-speed shear emulsification at 25-30 °C for 5-10 min, add 25wt% glutaraldehyde, cure for 1-2 h to form microcapsules, and after centrifugal washing and freeze-drying, obtain white powdery zinc borate-silicone hybrid capsules.

[0009] Preferably, the mass ratio of mesoporous silica, zinc nitrate and boric acid in step A1 is 5:2:1.2.

[0010] Preferably, the mass ratio of the surface-modified nanoparticles, polyvinyl alcohol and glutaraldehyde in step A3 is 10:1:0.2.

[0011] Preferably, the preparation method of the dopamine derivative-graphene quantum dot composite includes the following steps: B1. Dissolve dopamine hydrochloride in MES buffer solution, add lauric acid and mix evenly, then add 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, stir in an ice bath for 20-40 min, and react at 25 °C in the dark for 20-24 h to generate dopamine-lauric acid derivative; B2. Dissolve the dopamine-lauric acid derivative in N,N-dimethylformamide, add nitrogen-doped graphene quantum dots and ultrasonically disperse, reflux at 80 °C for 6-8 h, dialyze to remove free nitrogen-doped graphene quantum dots, and freeze-dry to obtain the dopamine derivative-graphene quantum dot composite.

[0012] Preferably, the mass ratio of dopamine hydrochloride, lauric acid and nitrogen-doped graphene quantum dots is 1:1.2:0.5.

[0013] Preferably, the particle size of the nitrogen-doped graphene quantum is 3-5 nm, the N content is 5-8 at%, and it is pretreated with NaOH to enhance the surface negative charge and promote the combination with the dopamine-lauric acid derivative.

[0014] A preparation method of a PET film with hot melt adhesive on both sides includes the following steps: S1. First, melt and mix EVA resin, EMA resin and petroleum resin at 160-170 °C, then add MAH-g-EVA and microcrystalline wax and continue to mix. After cooling to 140 °C, add zinc borate-silicone hybrid capsules, and finally add the dopamine derivative-graphene quantum dot composite and antioxidant, and stir for 20-40 min to ensure uniform dispersion to obtain a modified EVA layer material; S2. First, make an adhesion layer on both sides of the PET substrate by dip coating method, and dry it in a suspension oven at a controlled temperature range of 50-120 °C; S3. Pass the modified EVA layer through the first extruder and laminate it on one side of the adhesion layer, and pass the modified EVA layer through the second extruder and laminate it on the other side of the adhesion layer to obtain a PET film with hot melt adhesive on both sides.

[0015] The beneficial effects of the present invention: The PET film with hot melt adhesive on both sides of the present invention comprises a PET substrate. An adhesion layer formed by a waterborne acrylate-modified polyurethane emulsion is coated on both sides of the PET substrate. A modified EVA adhesive layer is laminated and compounded on the outer side of the adhesion layer. The PET substrate can endow the composite material with stronger toughness, stiffness and a certain degree of puncture resistance. The adhesion layer can ensure the adhesion of the modified EVA adhesive layer to the PET substrate under high and low temperatures, high humidity and other conditions. The modified EVA adhesive layer is blended with EMA resin, petroleum resin and EVA resin, and modified substances such as MAH-g-EVA, microcrystalline wax, zinc borate-silicone hybrid capsules and dopamine derivative-graphene quantum dot composites are added, so that the modified EVA adhesive layer has good bonding performance and aging resistance.

[0016] Among them, the EVA resin provides basic bonding performance. The EMA resin can enhance the adhesion force on the polar surface and improve the resistance to heat and humidity. The petroleum resin plays a role in increasing viscosity, reducing costs and improving the initial tack. MAH-g-EVA can enhance the chemical bonding ability with polar materials (such as metals and glass). The microcrystalline wax adjusts the melt fluidity and reduces the internal stress. The zinc borate-silicone hybrid capsules and the dopamine derivative-graphene quantum dot composites work together to enhance the cohesion and the interfacial bonding force, thereby improving the bonding performance of the material, and at the same time improving the resistance of the material to heat and humidity aging and ultraviolet resistance.

[0017] The zinc borate-silicone hybrid capsules of the present invention are prepared by loading zinc borate nanoparticles on a mesoporous silica template, grafting a vinyl-containing silane coupling agent on the surface, and then encapsulating them into 1-2 μm capsules through a microemulsion technology. When heated, the zinc borate nanoparticles are released, forming a coordination bond with the carboxyl group of EVA to enhance the cohesion. The silane component migrates to the interface to form a Si-O-Si network, improving the resistance to heat and humidity aging. The capsule structure prevents the premature degradation of the additives. The dopamine derivative-graphene quantum dot composites of the present invention are prepared by condensing dopamine with lauric acid to generate an amphoteric polymer, and then self-assembling and loading nitrogen-doped graphene quantum dots through π-π stacking. The catechol structure of the dopamine-lauric acid derivative mimics the mussel adhesion protein, enhancing the interfacial bonding force. The defect sites of the nitrogen-doped graphene quantum dots capture free radicals, and cooperate with antioxidants to improve the ultraviolet resistance. The long-chain alkyl group improves the compatibility with EVA. Description of the Drawings

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, for those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0019] Figure 1 It is a schematic structural diagram of the PET film with hot melt adhesive on both sides of the present invention; Figure 2 Schematic process flow diagram for the preparation of a PET film with hot melt adhesive on both sides according to the present invention; Figure 3 Transmission electron microscope image of mesoporous silica and zinc borate - organosilicon hybrid capsules in Example 1 of the present invention; Figure 4 Transmission electron microscope image of the dopamine derivative - graphene quantum dot composite prepared in Example 2 of the present invention. Detailed implementation manners

[0020] Next, in combination with the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.

[0021] Example 1 A zinc borate - organosilicon hybrid capsule, after loading zinc borate nanoparticles with mesoporous silica as a template, grafting a vinyl - containing silane coupling agent on the surface, and then encapsulating it into 1 - 2 μm capsules through microemulsion technology. Its specific preparation method includes the following steps: A1. Immerse 10 g of mesoporous silica in 100 ml of an ethanol solution of 0.1 M zinc nitrate and 0.2 M boric acid, adjust the pH to 6.5 with acetic acid, ultrasonicate for 30 min, and perform a hydrothermal reaction at 80 °C for 5 h to form zinc borate - loaded nanoparticles; A2. Disperse the above nanoparticles in 50 ml of an ethanol solution of 10%Vol vinyltrimethoxysilane, add 0.5 ml of ammonia water for catalysis, and reflux at 60 °C for 12 h to obtain surface - modified nanoparticles; A3. Disperse 10 g of the surface - modified nanoparticles in 27.5 ml of paraffin oil to obtain an oil phase, mix 100 ml of a 1 wt% polyvinyl alcohol solution and 10 ml of a 0.5 wt% sodium dodecyl sulfate solution to obtain an aqueous phase, adjust the pH of the aqueous phase to 4 - 5 with acetic acid, then mix the oil phase and the aqueous phase, add 2 ml of an emulsifier composed of span 80 and tween 80 in a volume ratio of 7:3, perform high - speed shear emulsification at 28 °C for 8 min, add 1 ml of 25 wt% glutaraldehyde, cure for 2 h to form microcapsules, and after centrifugal washing and freeze - drying, obtain white powdery zinc borate - organosilicon hybrid capsules.

[0022] Perform transmission electron microscope analysis on the mesoporous silica before and after modification to obtain a transmission electron microscope image as shown in Figure 3As shown, before modification, the mesoporous silica presented a monodisperse spherical morphology with relatively uniform particle sizes, 180 - 200 nm in diameter. However, the surface was rough. After modification, a distinct core - shell structure appeared. Meanwhile, the inner - core mesopores decreased and the surface became smoother. The outer layer was a micro - capsule shell layer with a thickness of 20 - 30 nm, indicating that the mesoporous silica was successfully loaded and a micro - capsule shell was formed on the surface.

[0023] Example 2 A dopamine derivative - graphene quantum dot composite. Dopamine is condensed with lauric acid to generate an amphoteric polymer, and then nitrogen - doped graphene quantum dots are loaded through π - π stacking self - assembly. The specific preparation method includes the following steps: B1. Dissolve 2.0 g of dopamine hydrochloride in 10 ml of MES buffer solution, add 2.3 g of lauric acid and mix evenly. Then add 0.5 g of 1 - ethyl - 3 - (3 - dimethylaminopropyl) carbodiimide and 0.2 g of N - hydroxysuccinimide. Stir in an ice bath for 30 min and react at 25 °C in the dark for 24 h to generate dopamine - lauric acid derivative. B2. Add nitrogen - doped graphene quantum dots with a particle size of 3 - 5 nm and an N content of 5 - 8 at% to 0.1 M NaOH solution, react at 50 °C for 3 h, then filter, wash and dry. Dissolve 5.6 g of dopamine - lauric acid derivative in 20 ml of N,N - dimethylformamide, add 1.1 g of nitrogen - doped graphene quantum dots, ultrasonically disperse, reflux at 80 °C for 8 h, dialyze to remove free nitrogen - doped graphene quantum dots, and freeze - dry to obtain the dopamine derivative - graphene quantum dot composite.

[0024] The prepared dopamine derivative - graphene quantum dot composite was analyzed by transmission electron microscopy, and the transmission electron micrograph is as Figure 4 shown. From Figure 4 (a), it can be seen that the nitrogen - doped graphene quantum dots are evenly attached to the surface of the dopamine - lauric acid derivative without aggregation, with a particle size of 3 - 5 nm. High - resolution Figure 4 (b) shows the lattice fringes of the nitrogen - doped graphene quantum dots with a spacing of 0.21 nm, corresponding to the graphene (100) plane.

[0025] Example 3 A PET film with hot melt adhesive on both sides comprises a PET substrate. Adhesion layers are coated on both sides of the PET substrate, and a modified EVA adhesive layer is laminated on the outside of the adhesion layers. The adhesion layer is a waterborne acrylate-modified polyurethane emulsion. The modified EVA adhesive layer comprises the following raw materials in parts by weight: 70 parts of EVA resin, 18 parts of EMA resin, 22 parts of petroleum resin, 5 parts of MAH-g-EVA, 9 parts of microcrystalline wax, 6 parts of zinc borate-silicone hybrid capsule, 4 parts of dopamine derivative-graphene quantum dot composite, 0.6 part of antioxidant 1010, and 0.2 part of antioxidant 168. The petroleum resin is a C5 / C9 mixture type. The waterborne acrylate-modified polyurethane emulsion is obtained by adding ammonium persulfate to initiate a polymerization reaction after mixing acrylate monomers with polyurethane emulsion. The zinc borate-silicone hybrid capsule is obtained in Example 1. The dopamine derivative-graphene quantum dot composite is obtained in Example 2.

[0026] The preparation method of the above PET film with hot melt adhesive on both sides comprises the following steps: S1. First, melt and mix the EVA resin, EMA resin, and petroleum resin at 165 °C, then add MAH-g-EVA and microcrystalline wax and continue to mix. After cooling to 140 °C, add the zinc borate-silicone hybrid capsule. Finally, add the dopamine derivative-graphene quantum dot composite, antioxidant 1010, and antioxidant 168, and stir for 30 min to ensure uniform dispersion to obtain the modified EVA layer material. S2. First, make adhesion layers on both sides of the PET substrate by dip coating method, and dry them in a suspension oven at a controlled temperature range of 80 °C. S3. Laminating the modified EVA layer on one side of the adhesion layer through the first extruder, and laminating the modified EVA layer on the other side of the adhesion layer through the second extruder to obtain the PET film with hot melt adhesive on both sides.

[0027] Example 4 A PET film with hot melt adhesive on both sides comprises a PET substrate. Adhesion layers are coated on both sides of the PET substrate, and a modified EVA adhesive layer is laminated on the outside of the adhesion layers. The adhesion layer is a waterborne acrylate-modified polyurethane emulsion. The modified EVA adhesive layer comprises the following raw materials in parts by weight: 60 parts of EVA resin, 20 parts of EMA resin, 20 parts of petroleum resin, 6 parts of MAH-g-EVA, 8 parts of microcrystalline wax, 8 parts of zinc borate-silicone hybrid capsule, 3 parts of dopamine derivative-graphene quantum dot composite, 0.8 part of antioxidant 1010, and 0.2 part of antioxidant 168. The petroleum resin is a C5 / C9 mixture type. The waterborne acrylate-modified polyurethane emulsion is obtained by adding ammonium persulfate to initiate a polymerization reaction after mixing acrylate monomers with polyurethane emulsion. The zinc borate-silicone hybrid capsule is obtained in Example 1. The dopamine derivative-graphene quantum dot composite is obtained in Example 2.

[0028] The preparation method of the above-mentioned PET film with hot melt adhesive on both sides comprises the following steps: S1. First, melt and mix EVA resin, EMA resin, and petroleum resin at 160°C, then add MAH-g-EVA and microcrystalline wax and continue mixing. After cooling to 140°C, add zinc borate-silicone hybrid capsules. Finally, add dopamine derivative-graphene quantum dot composite, antioxidant 1010, and antioxidant 168, and stir for 40 min to ensure uniform dispersion to obtain the modified EVA layer material; S2. First, make adhesion layers on both sides of the PET substrate by dip coating method, and dry them in a suspension oven at a controlled temperature range of 50°C; S3. Through the first extruder, the modified EVA layer is laminated and compounded onto one side of the adhesion layer, and through the second extruder, the modified EVA layer is laminated and compounded onto the other side of the adhesion layer to obtain the PET film with hot melt adhesive on both sides.

[0029] Example 5 A PET film with hot melt adhesive on both sides comprises a PET substrate. Adhesion layers are coated on both sides of the PET substrate, and a modified EVA adhesive layer is laminated and compounded on the outside of the adhesion layers. The adhesion layer is a waterborne acrylate-modified polyurethane emulsion. The modified EVA adhesive layer comprises the following raw materials in parts by weight: 80 parts of EVA resin, 15 parts of EMA resin, 25 parts of petroleum resin, 4 parts of MAH-g-EVA, 10 parts of microcrystalline wax, 5 parts of zinc borate-silicone hybrid capsules, 5 parts of dopamine derivative-graphene quantum dot composite, 0.4 part of antioxidant 1010, and 0.1 part of antioxidant 168; the petroleum resin is a C5 / C9 mixture type. The waterborne acrylate-modified polyurethane emulsion is obtained by mixing acrylate monomers with polyurethane emulsion and then adding ammonium persulfate to initiate a polymerization reaction; the zinc borate-silicone hybrid capsules are obtained in Example 1; the dopamine derivative-graphene quantum dot composite is obtained in Example 2.

[0030] The preparation method of the above-mentioned PET film with hot melt adhesive on both sides comprises the following steps: S1. First, melt and mix EVA resin, EMA resin, and petroleum resin at 170°C, then add MAH-g-EVA and microcrystalline wax and continue mixing. After cooling to 140°C, add zinc borate-silicone hybrid capsules. Finally, add dopamine derivative-graphene quantum dot composite, antioxidant 1010, and antioxidant 168, and stir for 20 min to ensure uniform dispersion to obtain the modified EVA layer material; S2. First, make adhesion layers on both sides of the PET substrate by dip coating method, and dry them in a suspension oven at a controlled temperature range of 120°C; S3. The modified EVA layer is laminated and compounded onto the adhesion layer on one side through the first extruder, and the modified EVA layer is laminated and compounded onto the adhesion layer on the other side through the second extruder to obtain a PET film with hot melt adhesive on both sides.

[0031] Comparative Example 1 A PET film with hot melt adhesive on both sides includes a PET substrate. Adhesion layers are coated on both sides of the PET substrate, and a modified EVA adhesive layer is laminated and compounded on the outside of the adhesion layers. The adhesion layer is an aqueous acrylate-modified polyurethane emulsion. The modified EVA adhesive layer includes the following raw materials in parts by weight: 70 parts of EVA resin, 18 parts of EMA resin, 22 parts of petroleum resin, 5 parts of MAH-g-EVA, 9 parts of microcrystalline wax, 6 parts of zinc borate-silicone hybrid capsules, 4 parts of dopamine derivative-graphene quantum dot composite, 0.6 part of antioxidant 1010, and 0.2 part of antioxidant 168. The petroleum resin is a C5 / C9 mixture type. The aqueous acrylate-modified polyurethane emulsion is obtained by mixing acrylate monomers with a polyurethane emulsion and then adding ammonium persulfate to initiate a polymerization reaction. The dopamine derivative-graphene quantum dot composite is obtained in Example 2.

[0032] The preparation method of the above PET film with hot melt adhesive on both sides includes the following steps: S1. First, the EVA resin, EMA resin, and petroleum resin are melt-mixed at 165 °C, then MAH-g-EVA and microcrystalline wax are added and mixed continuously. After cooling to 140 °C, the dopamine derivative-graphene quantum dot composite, antioxidant 1010, and antioxidant 168 are added, and stirred for 30 min to ensure uniform dispersion, obtaining a modified EVA layer material; S2. Through the dip coating method, adhesion layers are made on both sides of the PET substrate first, and dried in a suspension oven at a controlled temperature range of 80 °C; S3. The modified EVA layer is laminated and compounded onto the adhesion layer on one side through the first extruder, and the modified EVA layer is laminated and compounded onto the adhesion layer on the other side through the second extruder to obtain a PET film with hot melt adhesive on both sides.

[0033] Comparative Example 2 A PET film with hot melt adhesive on both sides, comprising a PET substrate, with an adhesion layer coated on both sides of the PET substrate, and a modified EVA adhesive layer laminated and compounded on the outer side of the adhesion layer. The adhesion layer is a waterborne acrylate-modified polyurethane emulsion. The modified EVA adhesive layer comprises the following raw materials in parts by weight: 70 parts of EVA resin, 18 parts of EMA resin, 22 parts of petroleum resin, 5 parts of MAH-g-EVA, 9 parts of microcrystalline wax, 6 parts of zinc borate-silicone hybrid capsules, 4 parts of dopamine derivative-graphene quantum dot composites, 0.6 part of antioxidant 1010, and 0.2 part of antioxidant 168; the petroleum resin is a C5 / C9 mixture type, and the waterborne acrylate-modified polyurethane emulsion is obtained by mixing acrylate monomers with polyurethane emulsion and then adding ammonium persulfate to initiate a polymerization reaction; the zinc borate-silicone hybrid capsules are obtained in Example 1.

[0034] The preparation method of the above PET film with hot melt adhesive on both sides comprises the following steps: S1. First, melt and mix EVA resin, EMA resin, and petroleum resin at 165 °C, then add MAH-g-EVA and microcrystalline wax and continue to mix. After cooling to 140 °C, add zinc borate-silicone hybrid capsules, antioxidant 1010, and antioxidant 168, and stir for 30 min to ensure uniform dispersion to obtain the modified EVA layer material; S2. First, make an adhesion layer on both sides of the PET substrate by dip coating method, and dry it in a suspension oven at a controlled temperature range of 80 °C; S3. Laminate and compound the modified EVA layer onto one side of the adhesion layer through the first extruder, and laminate and compound the modified EVA layer onto the other side of the adhesion layer through the second extruder to obtain a PET film with hot melt adhesive on both sides.

[0035] Performance testing I. Bonding performance test Perform a bonding performance test on the PET films with hot melt adhesive on both sides prepared in Examples 3 - 4 and Comparative Examples 1 - 2. The test standards are ASTM D1876 (T-peel strength) and ASTM D3330 (180° peel strength), and the results are shown in Table 1 below.

[0036] Table 1 Test results of the bonding performance of the PET film with hot melt adhesive on both sides It can be seen from the data in Table 1 that by adding zinc borate-silicone hybrid capsules alone, the cohesive strength is improved (through Zn 2+(coordination bond), but the improvement of interfacial adhesion is limited. Adding dopamine derivative-graphene quantum dot composite alone significantly enhances the interfacial binding (catechol chemical bond), but the modulus improvement at high temperature is insufficient. The bonding strengths of Examples 3 to 5 are significantly higher than those added alone in the two comparative examples, proving that zinc borate and dopamine derivative have complementary enhancement and there is a synergistic effect.

[0037] II. Aging Resistance Performance Test The PET films with hot melt adhesives on both sides prepared in Examples 3 to 4 and Comparative Examples 1 and 2 were subjected to aging resistance tests. The test standards were: ISO 9142 (humid heat aging, 85°C / 85% RH, 500 h, cycle period: 8 h heating / 16 h condensation) and ASTM G154 (UV accelerated aging, QUV, 300 h, UVA-340 lamp, 0.76 W / m² @ 340 nm, 60°C irradiation / 50°C condensation cycle). Then, their 180° peel strengths were tested according to ASTM D3330, and the peel strength retention rates were calculated. The results are shown in Table 2 below.

[0038] Table 2 Aging Resistance Performance Test of PET Films with Hot Melt Adhesives on Both Sides It can be seen from the data in Table 2 that adding zinc borate-silicone hybrid capsules alone mainly improves the wet heat stability (siloxane barrier effect) and has weak UV protection. Adding dopamine derivative-graphene quantum dot composite alone, the ultraviolet absorption of nitrogen-doped graphene quantum dots dominates the UV aging resistance, but the protection in a humid heat environment is insufficient. Examples 3 to 5 show the best performance under both aging conditions due to the combined action of the siloxane network and quantum dot free radical capture.

[0039] In the description of this specification, the descriptions referring to terms such as "one embodiment", "example", "specific example", etc. mean that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in a suitable manner in any one or more embodiments or examples.

[0040] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art of this industry should understand that the present invention is not limited by the above embodiments. The above embodiments and the descriptions in the specification only illustrate the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention will have various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed.

Claims

1. A PET film with hot melt adhesive on both sides, characterized in that, It includes a PET substrate, with an adhesion layer coated on both sides of the PET substrate, and a modified EVA adhesive layer laminated by casting on the outside of the adhesion layer. The adhesion layer is an aqueous acrylate-modified polyurethane emulsion. The modified EVA adhesive layer comprises the following raw materials in parts by weight: 60-80 parts of EVA resin, 15-20 parts of EMA resin, 20-25 parts of petroleum resin, 4-6 parts of MAH-g-EVA, 8-10 parts of microcrystalline wax, 5-8 parts of zinc borate-silica hybrid capsules, 3-5 parts of dopamine derivative-graphene quantum dot composite, and 0.5-1 part of antioxidant; The zinc borate-silica hybrid capsules are prepared by loading zinc borate nanoparticles with mesoporous silica as a template, grafting a vinyl-containing silane coupling agent on the surface, and then encapsulating them into 1-2 μm capsules through a microemulsion technique; The dopamine derivative-graphene quantum dot composite is prepared by condensing dopamine with lauric acid to form an amphoteric polymer, and then loading nitrogen-doped graphene quantum dots through π-π stacking self-assembly.

2. The PET film with hot melt adhesive on both sides according to claim 1, wherein The aqueous acrylate-modified polyurethane emulsion is obtained by mixing acrylate monomers with polyurethane emulsion and then adding ammonium persulfate to initiate a polymerization reaction.

3. The PET film with hot melt adhesive on both sides according to claim 1, wherein, The antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 3-4:

1.

4. The PET film with hot melt adhesive on both sides according to claim 1, characterized in that, The preparation method of the zinc borate-silica hybrid capsules comprises the following steps: A1. Immerse mesoporous silica in an ethanol solution of 0.1M zinc nitrate and 0.2M boric acid, adjust the pH to 6.5 with acetic acid, ultrasonicate for 20-40 min, and perform a hydrothermal reaction at 80°C for 4-6 h to form zinc borate-loaded nanoparticles; A2. Disperse the above nanoparticles in an ethanol solution of vinyltrimethoxysilane, add ammonia water for catalysis, and reflux at 60°C for 10-12 h to obtain surface-modified nanoparticles; A3. Disperse the surface-modified nanoparticles in paraffin oil at a mass ratio of 1:2.5 to obtain an oil phase, mix a 1wt% polyvinyl alcohol solution and a 0.5wt% sodium dodecyl sulfate solution to obtain an aqueous phase, adjust the pH of the aqueous phase to 4-5 with acetic acid, then mix the oil phase and the aqueous phase at a volume ratio of 1:4, add an emulsifier composed of span 80 and tween 80 at a volume ratio of 7:3, perform high-speed shear emulsification at 25-30°C for 5-10 min, add 25wt% glutaraldehyde, cure for 1-2 h to form microcapsules, and after centrifugal washing and freeze-drying, obtain white powdery zinc borate-silica hybrid capsules.

5. The PET film with hot melt adhesive on both sides according to claim 4, characterized in that, In the step A1, the mass ratio of mesoporous silica, zinc nitrate, and boric acid is 5:2:1.

2.

6. The PET film with hot melt adhesive on both sides according to claim 4, characterized in that, In the step A3, the mass ratio of the surface-modified nanoparticles, polyvinyl alcohol, and glutaraldehyde is 10:1:0.

2.

7. The PET film with hot melt adhesive on both sides according to claim 1, characterized in that, The preparation method of the dopamine derivative-graphene quantum dot composite comprises the following steps: B1. Dissolve dopamine hydrochloride in MES buffer solution, add lauric acid and mix evenly, then add 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, stir in an ice bath for 20-40 min, and react in the dark at 25°C for 20-24 h to generate dopamine-lauric acid derivatives; B2. Dissolve the dopamine - lauric acid derivative in N,N - dimethylformamide, add nitrogen - doped graphene quantum dots and ultrasonically disperse them, reflux at 80 °C for 6 - 8 h, dialyze to remove free nitrogen - doped graphene quantum dots, and freeze - dry to obtain the dopamine derivative - graphene quantum dot composite.

8. The PET film with hot melt adhesive on both sides according to claim 7, characterized in that, The mass ratio of the dopamine hydrochloride, lauric acid, and nitrogen - doped graphene quantum dots is 1:1.2:0.

5.

9. The PET film with hot melt adhesive on both sides according to claim 7, wherein, The nitrogen - doped graphene quantum dots have a particle size of 3 - 5 nm and an N content of 5 - 8 at%. They are pretreated with NaOH to enhance the surface negative charge and promote the binding with the dopamine - lauric acid derivative.

10. A method for preparing a PET film with hot melt adhesive on both sides according to any one of claims 1 to 9, characterized in that, It includes the following steps: S1. First, melt - mix EVA resin, EMA resin, and petroleum resin at 160 - 170 °C, then add MAH - g - EVA and microcrystalline wax and continue mixing. After cooling to 140 °C, add the zinc borate - organosilica hybrid capsule, and finally add the dopamine derivative - graphene quantum dot composite and antioxidant, and stir for 20 - 40 min to ensure uniform dispersion to obtain the modified EVA layer material. S2. First, apply an adhesion layer on both sides of the PET substrate by dip - coating method, and dry it in a suspension oven at a controlled temperature range of 50 - 120 °C. S3. Extrude the modified EVA layer and laminate it onto one side of the adhesion layer through the first extruder, and extrude the modified EVA layer and laminate it onto the other side of the adhesion layer through the second extruder to obtain a PET film with hot - melt adhesive on both sides.